Download presentation
Presentation is loading. Please wait.
1
Forming a Quadratic Equation with Given Roots
2
Miss Chan, I have learnt how to solve a quadratic equation, but how can I form a quadratic equation from two given roots? We can form the equation by reversing the process of solving a quadratic equation by the factor method.
3
Consider the following example:
Solve an equation x2 – 4x + 3 = 0 (x – 1)(x – 3) = 0 x – 1 = 0 or x – 3 = 0 x = 1 or x = 3
4
Form an equation from two given roots
Consider the following example: Form an equation from two given roots (x – 1)(x – 3) = 0 Reversing the process x – 1 = 0 or x – 3 = 0 x = 1 or x = 3
5
∴ The quadratic equation is x2 – 4x + 3 = 0.
Now, let’s study the steps of forming a quadratic equation from given roots (1 and 3) again. x = 1 or x = 3 Note this key step. x – 1 = 0 or x – 3 = 0 (x – 1)(x – 3) = 0 x2 – 4x + 3 = 0 ∴ The quadratic equation is x2 – 4x + 3 = 0.
6
In general, Roots , (x – )(x – ) = 0 Quadratic Equation α β α β
7
For example, Roots , (x – )(x – ) = 0 Quadratic Equation 1 2 1 2
8
, (x – )(x – ) = 0 –4 (x – )[x – ] = 0 α 1 (–4) β 2 For example, Roots
Quadratic Equation –4 Quadratic Equation (x – )[x – ] = 0 α 1 (–4) β 2
9
In general, If α and β are the roots of a quadratic equation in x, then the equation is: (x – α)(x – β) = 0
10
Follow-up question In each of the following, form a quadratic equation in x with the given roots, and write the equation in the general form. (a) –1, –5 (b) (a) The required quadratic equation is [x – (–1)][x – (–5)] = 0 (x + 1)(x + 5) = 0 x2 + x + 5x + 5 = 0 x2 + 6x + 5 = 0
11
(b) The required quadratic equation is
12
but it is too tedious to expand the left hand side of the equation
I am trying to form a quadratic equation whose roots are and , In fact, there is another method to form a quadratic equation. It helps you form this quadratic equation.
13
Using Sum and Product of Roots
Suppose α and β are the roots of a quadratic equation. Then, the equation can be written as: (x – )(x – ) = 0 x2 – x – x + = 0 By expansion x2 – ( + )x + = 0 Sum of roots Product of roots
14
Using Sum and Product of Roots
Suppose α and β are the roots of a quadratic equation. Then, the equation can be written as: x2 – (sum of roots)x + product of roots = 0
15
Let’s find the quadratic equation whose roots are and .
∴ The required quadratic equation is x2 – (sum of roots)x + product of roots = 0
16
Follow-up question Form a quadratic equation in x whose roots are and (Write your answer in the general form.)
17
Follow-up question Form a quadratic equation in x whose roots are and (Write your answer in the general form.) ∴ The required quadratic equation is
Similar presentations
© 2025 SlidePlayer.com. Inc.
All rights reserved.